2021
DOI: 10.1186/s12936-021-03623-3
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive mobile application tool for disease surveillance, workforce management and supply chain management for Malaria Elimination Demonstration Project

Abstract: Background Health care technologies are now offering accountability, quality, robustness, and accuracy in disease surveillance and health care delivery programmes. With the advent of mobile hand-held devices, these technologies have become more accessible and adaptable for use by field staff working in remote areas. The Malaria Elimination Demonstration Project started collection of data and conduct of routine operations using paper-based reporting systems. Observing the need for a robust and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…This was because of MEDP’s strong focus on these indicators since the beginning of the field operations [ 15 , 18 ]. Additionally, the mobile application surveillance tool (SOCH) was introduced in July 2018, which further improved the overall accountability, reporting, and supply chain management systems [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was because of MEDP’s strong focus on these indicators since the beginning of the field operations [ 15 , 18 ]. Additionally, the mobile application surveillance tool (SOCH) was introduced in July 2018, which further improved the overall accountability, reporting, and supply chain management systems [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the adequate stock was available in 93.3% of VMW areas during the entire year and 97.8% in the high-transmission season. It was observed that despite using the Solutions for Community Healthworkers (SOCH) mobile application [ 27 ], few situations of medicines and diagnostics stock-outs arose due to interruption in raising of stock requests by the VMWs. These interruptions included human error, mobile network, and hardware issues.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the malaria control system (MCS) used in Mangaluru city, Karnataka, was able to document a significant reduction in malaria incidence in terms of slide positivity rate (SPR) and annual parasite incidence (API) over five years, during which, the system was employed [ 7 ]. Similarly, the Solution for Community Health Workers (SOCH) mobile application deployed in the Mandla district of Madhya Pradesh documented a 91% reduction of indigenous malaria cases in the district [ 8 ]. These reductions were possible due to regular and timely intervention by the respective health authorities in terms of enforcing vector control measures.…”
Section: Discussionmentioning
confidence: 99%
“…This system collects surveillance data through an Android tablet with in-built geographical information system (GIS) tagging and transmits the data, which can be accessed through a web-based system [ 7 ]. Similarly, a mobile application tool known as SOCH (Solution for Community Health Workers) was implemented in 2017 for real-time malaria surveillance and reporting in the Mandla district of Madhya Pradesh [ 8 ]. Even in Northeast India, the FeverTracker app has recently been deployed for active malaria surveillance in 19 tribal villages in Tripura’s Dhalai district [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The National Vector Borne Disease Control Programme (NVBDCP) of India is the largest surveillance network in the world [ 2 ]. Despite a well-defined active and passive surveillance system and a decreasing trend in malaria cases, gross discrepancies between reported malaria incidence in India, and the estimated malaria cases in the WHO published World Malaria Report have been noted [ 10 , 11 ]. A recent study estimated malaria incidence to be four-fold greater than one million reported by the NVBDCP but three-fold less than 13 million estimated by the WHO, whereas the estimated deaths were 93-fold more than the average 313 deaths reported by the national malaria program in 2015-2016 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%